Product design improvement through design for manufacture and assembly (DFMA) and theory of inventive problem solving (TRIZ) - Rozali, Afzan (2010)
The goal of this project is to improve product design of consumer product by integrating Boothroyd Dewhurst Design for Manufacture and Assembly (DFMA) methodology with a Russian Theory of Inventive Problem Solving (TRIZ). The outcome of previous research has shown integrating several design tools has improved the reliability and reduce cost of the product. A consumer product was selected as a case study to evaluate the integration of both design tools. The Boothroyd Dewhurst Design for Manufacture and Assembly Methodology (DFMA) is used as a quantitative improvement tools. The powerful tool can reduce parts number of a product and is expressed in percentage. While, the Russian Theory of Inventive Problem Solving (TRIZ) is used to improve the design qualitatively. The results show that the integration of these tools can be a very powerful design tool for product design engineers in reducing cost by eliminating unnecessary parts while improving the ease of user handling and reliability of the consumer product.